THE EFFECT OF EXCLUSIVE BREAST-MILK COUNSELING ON PREGNANT WOMEN IN BREAST FEEDING IN THE WORKING AREA OF LAHEI II REGENCY OF NORTH BARITO - Achmad Rizal Rizal; Agus Jalpi Jalpi (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Baby given milk other than ASI has 17 times greater risk of experiencing diarrhea and 3 to 4 times more likely to be exposed to respiratory than babies who get breast milk. According to the data and the report of the Office of North Barito, coverage of exclusive breast feeding only 57.2% of the targets set in the amount of 80%. And according to data and reports KIA Lahei II public health scope of Exclusive breast feeding only amounted to 13.4%. The purpose of the study to find out the influence of health education on motivation against pregnant women in the exclusive breast feeding 0-6 month in the region of clinics Lahei II. Research methods using quasy experiment design with a non randomized control group pretest postest design. The sample is first pregnant women (G1) which are domiciled in the territory of origin and work of clinics Lahei II at the time the research was conducted. Sampling with purposive sampling, obtained 46 people are divided into groups of treatment and control. Data collection with interviews using questionnaire. The results of data analysis with Paired T Test with p = 0.000, there is a difference between the motivation of the respondent before with wellness counseling, and after p = 0,236 that means no difference between the control group motivation first measurement with measurement Second, as well as Unpaired T test Test with p = 0.001, there is a difference between the treatment groups with controls. It can be concluded that there is the influence of health education on motivation against pregnant women in the exclusive breast feeding.Keywords: Health Education, exclusive breast feeding, pregnant mothers motivation